THEORETICAL INVESTIGATIONS OF THE PROCESS OF INTERACTION WITH THE ENVIRONMENT OF A BULLDOZER BLADOW WITH VARIABLE GEOMETRY - Doudkin , Mikhail; Kim, Alina; Aukenova, Bekzat; Radenkov, Radoslav; Saveliev, Andrey; Andryukhov , Nikita (Journal of Applied Engineering Science, 2022)
The purpose of the work is to determine the rational parameters of a bulldozer blade with variable geometry, which provides an increase in productivity and an expansion of the bulldozer-terracer scope due to its universal adaptability of the cutting knife shape and the blade surface to the types and conditions of work. The existing studies of the interaction processes with the soil of specialized plough, for the most part, do not take into account specific features and do not allow a reasonable approach to the appointment of the main parameters of the dump with its universal adaptability. For this purpose, studies were carried out on the working process of excavating the soil with a blade of a new universal design, and above all, when digging the soil. The analysis of the ratios influence the central section length to the maximum working width, the inclination angles of the hinges in the longitudinal and transverse planes, and the rotation angle of the side sections on the variable geometric parameters of the blade, which determine its interaction with the ground, is carried out. At the same time, the theoretical dependences obtained based on the statics provisions of a granular medium with adhesion make it possible to analytically evaluate the dimensions and volume of the drag prism and the horizontal component of the resistance to digging with a blade with variable geometry.